2000
DOI: 10.1093/genetics/156.4.1585
|View full text |Cite
|
Sign up to set email alerts
|

Scooter, a New Active Transposon in Schizophyllum commune, Has Disrupted Two Genes Regulating Signal Transduction

Abstract: Two copies of scooter, a DNA-mediated transposon in the basidiomycetous fungus Schizophyllum commune, were characterized. Scooter is the first transposon isolated from S. commune. Scooter creates 8-bp target site duplications, comparable to members of the hAT superfamily, and has 32-bp terminal inverted repeats. Both copies of scooter are nonautonomous elements capable of movement. Southern blot hybridizations show that scooter-related sequences are present in all S. commune strains tested. Scooter-1 was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The spontaneous thn1 mutation of S. commune suppresses aerial hyphae and subsequent fruiting body formation (145,225). thn1 encodes a GTPase activating protein that negatively regulates G-protein signaling (226). Its deletion in S. commune revealed that thn1 is involved in multiple processes, such as the temporal coordination of clamp cell (see Glossary) formation, the production of certain metabolites, and the induction several hydrophobins (e.g., Sc3 [224]).…”
Section: Genetic Bases Of Fruiting Body Developmentmentioning
confidence: 99%
“…The spontaneous thn1 mutation of S. commune suppresses aerial hyphae and subsequent fruiting body formation (145,225). thn1 encodes a GTPase activating protein that negatively regulates G-protein signaling (226). Its deletion in S. commune revealed that thn1 is involved in multiple processes, such as the temporal coordination of clamp cell (see Glossary) formation, the production of certain metabolites, and the induction several hydrophobins (e.g., Sc3 [224]).…”
Section: Genetic Bases Of Fruiting Body Developmentmentioning
confidence: 99%
“…Together with a significant expression found in RNAseq data, Soroa could have a significant impact on the functions and expressions of genes. Several mutations induced by TE insertions were reported in fungi, with negative or positive effects [65,73]. However, an analysis of 625 publicly available fungal genomes [66] identified numerous overlaps between the TE remnants and coding genes, but had no correlation with gene function.…”
Section: The Hva Genome Is Mainly Composed Of Three Ltr-rt Lineagesmentioning
confidence: 99%